2011
DOI: 10.3727/096368910x528102
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem Cells and Electroacupuncture Downregulate the Inhibitor Molecules and Promote the Axonal Regeneration in the Transected Spinal Cord of Rats

Abstract: Our previous study has reported that electroacupuncture (EA) promotes survival, differentiation of bone marrow mesenchymal stem cells (MSCs), and functional improvement in spinal cord-transected rats. In this study, we further investigated the structural bases of this functional improvement and the potential mechanisms of axonal regeneration in injured spinal cord after MSCs and EA treatment. Five experimental groups, 1) sham control (Sham-control); 2) operated control (Op-control); 3) electroacupuncture treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 68 publications
1
58
0
4
Order By: Relevance
“…Recently, cell transplantation has been an attractive strategy to provide neurotrophic factors and permissive substrates for axonal extension, and remyelin regenerated or damaged axons after SCI (Xu and Onifer 2009). Different cell types, including neural stem cells (NSCs) (Rao and MayerProschel 2000), oligodendrocyte progenitor cells (OPCs) (Givogri, et al 2006), Schwann cells (SCs) (Oudega and Xu 2006;Xu et al 1997), olfactory ensheathing glial cells (OEGs) (Ma et al 2010), and marrow stroma cells (MSCs) (Ding, et al 2011) have been used as donor cells for transplantation after SCI.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, cell transplantation has been an attractive strategy to provide neurotrophic factors and permissive substrates for axonal extension, and remyelin regenerated or damaged axons after SCI (Xu and Onifer 2009). Different cell types, including neural stem cells (NSCs) (Rao and MayerProschel 2000), oligodendrocyte progenitor cells (OPCs) (Givogri, et al 2006), Schwann cells (SCs) (Oudega and Xu 2006;Xu et al 1997), olfactory ensheathing glial cells (OEGs) (Ma et al 2010), and marrow stroma cells (MSCs) (Ding, et al 2011) have been used as donor cells for transplantation after SCI.…”
Section: Introductionmentioning
confidence: 98%
“…Since cavity or gap formation is evident following SCI in rats and humans (Oudega and Xu, 2006; Xu and Onifer, 2009), cell transplantation into the lesion site is essential to provide permissive substrates for axonal extension through and beyond it. Different cell types, including neural stem cells (NSCs) (Fujimoto et al, 2012; Sandner et al, 2012), fate-restricted neural and glial precursors (NRPs and GRPs) (Cao et al, 2002; Hill et al, 2004; Mitsui et al, 2005), Schwann cells (SCs) (Deng et al, 2011; Xu et al, 1997; Xu et al, 1995b), olfactory ensheathing glial cells (OEGs) (Feron et al, 2005; Ma et al, 2010), and marrow stroma cells (MSCs) (Ding et al, 2011; Phinney and Isakova, 2005) have been used as donor cells for transplantation after SCI with variable degrees of success. Importantly, genetic modification of transplanted cells could be utilized for gene therapy to enhance morphological and functional restoration (Deng et al, 2011; Girard et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Electroacupuncture (EA) which originated in ancient China thousands of years ago is widely used as an adjuvant therapy for many diseases2021222324, especially neurological diseases, including CNS damage and demyelinating diseases. EA has long been used to treat MS in traditional Chinese medicine, but the therapeutic mechanism is still unclear.…”
mentioning
confidence: 99%
“…In this connection, EA on Governor Vessel (GV-EA) acupoints is commonly used to treat spinal cord injury because impairment of Governor Vessel is correlated with the damage of spinal cord in Chinese traditional medicine. Indeed, GV-EA has been shown to alleviate the secondary damage after spinal cord injury in animal models212225. Our previous studies have reported that GV-EA could promote the secretion of neurotrophin-3 (NT-3) in injured spinal cord222627.…”
mentioning
confidence: 99%